ANALISIS DAYA SAING EKONOMI ANTAR DAERAH DI PROVINSI SUMATERA SELATAN - Sukanto Sukanto (Jurnal Ekonomi Pembangunan, 2009)
This research is aimed to know a description of economic competitiveness in The Province of South Sumatra and to what extend the correlation between economic performance, local finance, and HDI to economic competitiveness. Data used is pooled data (2001-2005). The analysis are based on some measurements such as mean,Â  deviation standard, Klassen Typology and Rank Spearman. The findings show the form of new regency has lower ranking compare to old one. The top ranking of competitiveness is Palembang City, and the lower is OKU Timur Regency. The correlation between economic performance and economic competitiveness is 94,7 percent, while the correlation between local finance and economic competitiveness is 70,1 percent. finally, the correlation between HDI and economic competitiveness is 47,3 percent. Keywords: Economic Competitiveness, GDP, Economic Growth, Income Per Capita, Inflation, LocalÂ  Finance, Human Development Index (HDI).